PEMIKIRAN IBNU KHALDUN TENTANG KETENAGAKERJAAN DAN RELEVANSINYA DI INDONESIA - Darsi Ahmadan (LA RIBA: Jurnal Perbankan Syariah, 2022)
Ibn Khaldun's thoughts on employment and its relevance in Indonesia???, with the background of the problem, namely, the enactment of Law Number 13 of 2003, is part of the government's grand scenario to organize and negotiate common interests between employers, workers and the government. If companies have an interest in capital development, workers have an interest in increasing income, then the government secures the macro economy. Because without conducive conditions, the economy of a country will be shaken. Ibn Khaldun was a Muslim scientist who had many thoughts in various fields such as economics. In his economic sub-study on employment, which is contained in Muqadimah's book on the theory of value, division of labor and international trade, the law of supply and demand, consumption, production, money, trade cycles, public finance, and several macroeconomic discussions. The type of research is library research. The type of data used is primary data, namely all of Ibn Khaldun's works that discuss employment, both implied and explicit, as well as data on employment in Indonesia. While secondary data is related to formal objects and enrichment that discusses employment in Indonesia. From the results of the researcher's analysis, it is known that, firstly, Ibn Khaldun's rationale for the emergence of the employment system because, to meet basic personal (dharuri), secondary (hajiyyah) and tertiary (tahsinat) needs, as well as to meet the needs of many people (subjective mass), is called " tamawwul??? (company). then for that humans to meet personal needs and many people have to produce en masse, the more needs, the more they produce, the more alliances (employment) arise, this is because what drives humans instinctively to work, because they work as human intermediaries to get what they want. that God created. Second, the main points of Ibn Khaldun's thoughts on employment are that the concept of thought starts from production, namely one of the factors is labor, with its elaboration; there are three levels of division of labor, namely the community, industry and international levels. Next is the demand and supply of labor, labor wages, expansion of job opportunities, competence and technology. Third, Based on these points of view, it can be concluded that Ibn Khaldun's thoughts have relevance to employment in Indonesia today. The relevance is found in the constitution or positive law of Indonesia in Article 33 of the Basic Law (UUD) article 33 and Law Number 13 of 2003 concerning employment, namely first according to Khaldun about the nature of labor as mutualism, while in the Indonesian constitution it is reflected in the Constitution. Article 33 paragraph (1). Second, work competence at the community, industrial and international levels, in Indonesian regulations is regulated in law number 13 of 2003 articles 9, 10, 11, and 12. Third, expansion of job opportunities in Indonesian regulations is regulated in law number 13 of 2003. 2003 articles 39, 40 and 41. Fourth, the salary of Khaldun's workers is the benchmark for meeting basic living needs (dharuri) while Indonesian regulations adhere to the principle of meeting the needs of a decent living (KHL).